Community Involvemen Pemetaan Sumberdaya Manusia Pada Desa Wisata Cupak, Jombang - Maya Sofiana; Ayu Fauziah; Siti Nur Azizah; Dewi Rahmawati; Fardiana Fardiana; Elliza Firnanda; Dinda Arinal Haq; Halimatus Saleha (Universitas Maritim AMNI Semarang, 2023)
: Cupak Village is a village that has tremendous potential that can be developed. In addition to the cool air, there are several potentials, including (1) religious tourism at Dewi Kilisuci's hermitage site, (2) Sendang Widodaren, Sendang Drajad, and Mount Pucangan; (3) Agricultural tourism which produces Porang as a flour ingredient, Gadung for chips, Corn as food security; (4) accompanied by the manufacture of handicrafts from local raw materials such as woven pandanus. (5) Production of charcoal which can be developed into Carkol as an export commodity. (6) Camping ground. However, the problem faced is the lack of awareness of local residents in the use of tourism. Cupak Village also has abundant agricultural income but its income level can still be developed through socialization so it is hoped that this activity can immediately encourage tourism in Cupak Village and it is hoped that it can also increase Cupak Village's agricultural income. The purpose of this activity is to get an overview of the qualifications of Cupak Village Human Resources in utilizing tourism potential, processing agricultural products, managing businesses, and overcoming existing problems. To determine activities in HR development that will be carried out appropriately based on the results of HR mapping Cupak Village, Potential, Tourism, Religion, Development